Prospective Study of Serum 25-hydroxy Vitamin D and Tooth Loss. (July 2014) - Zhan, Y.; Samietz, S.; Holtfreter, B.; Hannemann, A.; Meisel, P.; Nauck, M.; Völzke, H.; Wallaschofski, H.; Dietrich, T.; Kocher, T.
Vitamin D deficiency and oral diseases (periodontitis, caries, and tooth loss) are highly prevalent in Germany. Previous studies suggested that vitamin D might be a modifiable and protective factor for periodontitis, caries, and tooth loss. However, prospective studies investigating such associations are limited. We explored the association between the concentration of serum 25-hydroxy vitamin D (25OHD) and incidence of tooth loss, progression of clinical attachment loss (CAL) ≥ 3 mm, and progression of restorative and caries status in a population-based longitudinal study. We analyzed data from 1, 904 participants from the Study of Health in Pomerania with a five-year follow-up. Generalized estimating equation models were applied to evaluate tooth-specific associations between serum 25OHD and incidence of tooth loss, progression of CAL ≥ 3 mm, and progression of restorative and caries status. Age, sex, education, smoking status, alcohol drinking, waist circumference, dental visit frequency, reasons of dental visit, vitamin D or calcium supplements, and season of blood draw were considered as confounders. Serum 25OHD was inversely associated with incidence of tooth loss. A significant dose-response relationship ( p = .0022) was observed across the quintiles of serum 25OHD. After adjusting for multiple confounders, each 10-µg/L increase of serum 25OHD was associated with a 13% decreased risk of tooth loss (risk ratio: 0.87; 95% confidence interval: 0.79, 0.96). The association was attenuated for changes of CAL ≥ 3 mm when adjusting for multiple confounders. No significant association was found between serum 25OHD and caries progression. Vitamin D might be a protective factor for tooth loss. The effect might partially be mediated by its effect on periodontitis.